Measuring the impact of COVID-19 and government policy responses on trade flow: The case of ASEAN countries - Quoc Viet Nguyen; Thi Thoan Nguyen; Vu Huy Le; Tuong Vy Phan; Ha Linh Bui; Phuong Thao Nguyen; Thi Hong Tham Do (Asian Development Bank Institute (ADBI), 2024)
The epidemic caused by the coronavirus disease (COVID-19) has affected international trade activities between Asian developing and emerging economies, especially the ASEAN region. This paper aims to examine and measure the impact of COVID-19 and government responses on trade flow using the gravity model of trade. Using the trade records of ten ASEAN countries exporting all over the world from January 2020 to December 2022, we find a negative impact of the COVID-19 pandemic on trade flow. However, ASEAN countries that participate in regional trade agreements (RTAs) have stronger trade flows than countries that do not participate. Finally, countries implementing effective COVID-19 policy responses exhibit a more favorable trade performance and improve their overall economic stability, particularly in the face of increasing COVID-19 burdens.
Keywords: F14; C54; D78; I18; O24; 330; COVID-19 policy responses; economic stability; emerging economies; regional trade agreement (RTA); trade flow